2014
DOI: 10.1530/ec-14-0042
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses to psychological stress: importance of adiposity in men aged 50–70 years

Abstract: We tested the hypothesis that overweight/obese men aged 50–70 years will have a greater salivary cortisol, salivary alpha amylase and heart rate (HR) responses to psychological stress compared with age matched lean men. Lean (BMI=20–25 kg/m2; n=19) and overweight/obese (BMI=27–35 kg/m2; n=17) men (50–70 years) were subjected to a well-characterised psychological stress (Trier Social Stress Test, TSST) at 1500 h. Concentrations of cortisol and alpha amylase were measured in saliva samples collected every 7–15 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 36 publications
3
21
1
Order By: Relevance
“…In contrast to the present results, the studies by Lorig et al [17] and Benson et al [21] demonstrated a main effect of obesity in the cortisol response. However, Jayasinghe et al [18], McInnis et al [20], and Therrien et al [19] indicated no significant difference in the cortisol response between obese and normal-weight women during the TSST which is in line with the present results.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In contrast to the present results, the studies by Lorig et al [17] and Benson et al [21] demonstrated a main effect of obesity in the cortisol response. However, Jayasinghe et al [18], McInnis et al [20], and Therrien et al [19] indicated no significant difference in the cortisol response between obese and normal-weight women during the TSST which is in line with the present results.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the studies by Benson et al [21], Jayasinghe et al [18], and Therrien et al [19] indicated a magnitude of the cortisol response between 82 and 372% increase to the TSST. Our study demonstrated a 275% increase in the cortisol concentration of both groups and a 327% increase in the obese individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To confirm this, serum testosterone and estradiol were detected in male BALB/c mice immunized with the HBV vaccine, but not statistical significant difference was found at the levels of two sex hormones between the fighting mice and the mice without fighting experience, suggesting that sex hormones might not be involved in the fighting-enhanced antibody response to vaccines. Because that exercise and psychological stress can activate the hypothalamic-pituitary-adrenal (corticosterone) response and the sympathetic nervous system (norepinephrine and epinephrine) response, resulting in a range of rapid physiological and behavioral responses (10,12), next the study tested whether fighting, a behavior complicated with intense exercise and psychological stress, might affect antibody production through the stress hormones. It was observed that administration with hydrocortisone or norepinephrine by intravenous injection to the tail significantly decreased rather than increased the levels of HBsAb to HBV vaccine in both the male and the female BALB/c mice.…”
Section: Discussionmentioning
confidence: 99%